2006
DOI: 10.1007/bf03344095
|View full text |Cite
|
Sign up to set email alerts
|

Association of pelvic endometriosis with alopecia universalis, autoimmune thyroiditis and multiple sclerosis

Abstract: An adult Caucasian female developed a previously unreported association of pelvic endometriosis (PE) with the triad of alopecia universalis (AU), autoimmune thyroiditis (AT) and multiple sclerosis (MS). Molecular human leukocyte antigen (HLA)-tissue typing of this subject showed the presence of the DR(2) 15 and DR(3) 17 alleles, which are associated to an increased risk of MS and AT, respectively. Clinical onset of AT followed withdrawal of corticosteroid treatment for AU, whereas MS become clinically evident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Previously, Alviggi et al described a single case of a Caucasian female patient affected by alopecia universalis, MS, autoimmune thyroiditis, and pelvic endometriosis. In this particular case, alopecia universalis occurred at the age of 13, while the onset of MS followed at the age of 27.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Alviggi et al described a single case of a Caucasian female patient affected by alopecia universalis, MS, autoimmune thyroiditis, and pelvic endometriosis. In this particular case, alopecia universalis occurred at the age of 13, while the onset of MS followed at the age of 27.…”
Section: Discussionmentioning
confidence: 99%
“…This so-called global immune dysregulation could account for the increased incidence of other systemic, autoimmune disorders for each ailment. For example, systemic lupus erythematosus and rheumatoid arthritis as well as other autoimmune inflammatory conditions, hypothyroidism, allergies, fibromyalgia, asthma, and multiple sclerosis are more common in women with endometriosis (15,16). In parallel, associations have been found between periodontal disease and systemic disorders such as diabetes mellitus (8,17), cardiovascular disease (18)(19)(20), pulmonary disease (21)(22)(23), and preterm delivery (22,(24)(25)(26)(27)(28)(29).…”
Section: Predictormentioning
confidence: 93%
“…Case reports have suggested co-morbidity of endometriosis with the autoimmune disorders alopecia universalis, autoimmune thyroiditis, multiple sclerosis, and autoimmune progesterone dermatitis,[10 11] and a comparative evaluation of clinical and humoral immunologic abnormalities between SLE and endometriosis has also suggested similarities. [12] A cross-sectional survey of women with endometriosis who were members of a national endometriosis support organization, compared to the general U.S. population, reported a prevalence odds ratio for SLE of 20.7 (CI=14.3-29.9) and for RA of 1.5 (CI=1.2-1.9);[13] however this survey was limited by its highly self-motivated study population with self-reported endometriosis and autoimmune diseases and lack of control for confounders.…”
Section: Introductionmentioning
confidence: 99%